2006
DOI: 10.1002/anie.200504465
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Electric Dipole Fields and the Induction of Hierarchical Form Developments in Fluorapatite–Gelatine Nanocomposites: A General Principle for Morphogenesis of Biominerals?

Abstract: The seeder of the pack: The electrical potential distribution (see phase image of an electron hologram) around the basal plane close to the prism faces of a hexagonal fluorapatite–gelatine nanocomposite seed influences the growth of the nanocomposite. The seed consists of elementary dipoles on the nanometer scale, which all have the same orientation along the c axis of the composite seed. Further form development of the seed leads to fractal patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
119
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 26 publications
1
119
1
Order By: Relevance
“…3) was achieved by diffusion of calcium -and orthophosphate + fluoride solutions from opposite sides into a tube filled with a gelatin gel. [444][445][446][447][448][449][450][451][452][453] The reasons for this phenomenon are not quite clear yet; besides, up to now, nothing has yet been reported on a possible biomedical application for such very unusual structural composites.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…3) was achieved by diffusion of calcium -and orthophosphate + fluoride solutions from opposite sides into a tube filled with a gelatin gel. [444][445][446][447][448][449][450][451][452][453] The reasons for this phenomenon are not quite clear yet; besides, up to now, nothing has yet been reported on a possible biomedical application for such very unusual structural composites.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…2) was achieved by diffusion of calcium-and orthophosphate ? fluoride-solutions from the opposite sides into a tube filled with a gelatin gel [366][367][368][369][370][371][372][373][374]. The reasons of this phenomenon are not quite clear yet; besides, up to now nothing has yet been reported on a possible biomedical application of such very unusual structural composites.…”
Section: Apatite-based Biocompositesmentioning
confidence: 99%
“…[4,[9][10][11][12][13][14] Kniep and co-workers have described a fluorapatite-gelatine system that resembles the biosystem hydroxyapatite-collagen in both bone and dentine. [13] Recently, Yamagishi et al have reported a paste of fluoridated hydroxyapatite that could be used to repair a small carious lesion. Although the interface between the precipitated layer from the paste and the tooth surface contains elongated crystals some of which are orientated towards the tooth surface, the unique enamel prism structure is not visible from the transmission electron microscopy (TEM) images.…”
mentioning
confidence: 97%